Individual Career Transitions of German Olympians During the COVID-19 Pandemic: An Application of the Scheme of Change for Sport Psychology Practice - Leisterer, S.; Lautenbach, F. (Zeitschrift für Sportpsychologie, 2021)
The COVID-19 pandemic can affect individual career transitions in athletes preparing for the Olympic Games (OG). This study reconstructs German Olympians` career transitions while preparing for the postponed OG in Tokyo, applying the Scheme of Change for Sport Psychology Practice (SCSPP). Eleven (age: M ± SD = 26.81 ± 2.92; three females) athletes provide insights into their career transitions according to the SCSPP framework. The athletes report changes (e. g., training, professional status, missing competitions) related to emotional tensions (e. g., relief vs. disappointment) and the effects on their decision-making processes (i. e., initial coping, acceptance, adaptation). The Olympians develop identities, commonly experience relief, and describe their optimism toward Tokyo 2021. No interviewee wants to quit because of COVID-19. While preparing for Tokyo 2021, the Olympians use emotion- (e. g., vacation) and problem-oriented coping (e. g., new routines). Based on our results, we discuss recommendations for sport psychology practice.